PENGARUH LEADER MEMBER EXCHANGE, SELF EFFICACY DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN (Studi Pada Karyawan Bagian Pabrikasi di PT. PG Candi Baru Sidoarjo) - VIA ERLITA, DINA; SURJANTI, JUN (Jurnal Ilmu Manajemen (JIM), 2018)
Abstract The purpose of this study examines the influence of leader member exchange, self efficacy, and job satisfaction on the employee performance in the manufacturing at PT. PG Candi Baru Sidoarjo. PLS is used to test the effect of all three on employee performance. The test results show that there is a significant positive influence of the leader member exchange on employee performance, but not with self efficacy and job satisfaction that has positive but not significant influence. The implication of this research is the company can improve its performance by using leader member exchange. Keywords: leader member exchange, self efficacy, job satisfaction, employee performance